Political cartoons as epideictic: Rhetorical analysis of two of the Charlie Hebdo political cartoons*. Issue 1 (2nd January 2017) - Bezanson, Mary Elizabeth
Abstract: On January 7, 2015, 12 people were killed during the bombing of the Charlie Hebdo offices. What makes this especially chilling was that the attack was launched against a newspaper for publishing images of Muhammad used for satiric commentary. The following day, CNN's Nick Thompson posted a series of political cartoons responding to the attack. Many employed the idiom, "The pen is mightier than the sword." This analysis focuses on two of the cartoons using that idiom: Linus MacLeod's "Powerful, More Powerful" and James Walmesley's "Pencil and Eraser." MacLeod's cartoon maintains a fidelity to the adage, in that he employs the image of a pen, while Walmseley instead depicts a pencil, the writing instrument more typically associated with a cartoonist's work. After a discussion of the history and nature of the idiom, this piece analyzes the comics by using the construction of narrative by Barry Brummett, and the construction of image offered by Molly Bang. The piece argues that the images function epideictically by praising freedom of speech and blaming terrorists.